THE NEW STRATEGY OF UZBEKISTAN IS THE POLITICAL VIEWS AND THEORIES ABOUT THE POLITICAL CULTURE OF PERSONNEL AND MANAGEMENT PERSONNEL (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article fully describes Uzbekistan's strategy, personnel, management personnel, political views, political culture, personnel responsibility, leadership responsibility, "democratic state", "legal state", "democratic society", "civil society", leadership activities, responsibilities and responsibilities.